Low-dose targeted radionuclide therapy synergizes with CAR T cells and enhances tumor response - Yang, Yanping; Vedvyas, Yogindra; Alcaina, Yago; Son, Ju Y.; Min, Irene M.; Jin, Moonsoo M. (Frontiers in Immunology, 2024)
Ionizing radiation has garnered considerable attention as a combination partner for immunotherapy due to its potential immunostimulatory effects. In contrast to the more commonly used external beam radiation, we explored the feasibility of combining chimeric antigen receptor (CAR) T cell therapy with targeted radionuclide therapy (TRT), which is achieved by delivering β-emitting 177 Lu-DOTATATE to tumor via tumor-infiltrating CAR T cells that express somatostatin receptor 2 (SSTR2). We hypothesized that the delivery of radiation to tumors could synergize with CAR T therapy, resulting in enhanced antitumor immunity and tumor response. To determine the optimal dosage and timing of 177 Lu-DOTATATE treatment, we measured CAR T cell infiltration and expansion in tumors longitudinally through positron emission tomography (PET) using a SSTR2specific positron-emitting radiotracer, 18 F-NOTA-Octreotide. In animals receiving CAR T cells and a low dose (2.5 Gy) of TRT following the administration of 177 Lu-DOTATATE, we observed a rapid regression of large subcutaneous tumors, which coincided with a dramatic increase in serum proinflammatory cytokines. Tumor burden was also reduced when a higher radiation dose (6 Gy) was delivered to the tumor. However, this higher dose led to cell death in both the tumor and CAR T cells. Our study suggests that there may exist an optimum range of TRT dosage that can enhance T cell activity and sensitize tumor cells to T cell killing, which may result in more durable tumor control compared to a higher radiation dose.